1980
DOI: 10.7326/0003-4819-93-4-533
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil, Doxorubicin, and Mitomycin (FAM) Combination Chemotherapy for Advanced Gastric Cancer

Abstract: Sixty-two patients with advanced measurable gastric cancer were treated with a combination chemotherapy program of 5-fluorouracil, doxorubicin, and mitomycin (FAM). Forty-two percent of patients achieved an objective partial response. The median duration of remission was 9 months and the median survival for responding patients, 12.5 months. The median survival for nonresponding patients was 3.5 months; all patients were dead by 8 months after initiation of therapy. The median survival of all 62 patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
107
2
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(115 citation statements)
references
References 7 publications
4
107
2
2
Order By: Relevance
“…Intravenous 5FU infusion [10] or in combination with other anticancer drugs, FAM [11], FAMTX [7] have been used for chemotherapy of advanced gastric cancer. Recently, Ajani reported that DCF therapy (a combination chemotherapy using docetaxel, CDDP and 5FU) showed a significant better survival than CF (CDDP þ 5FU) therapy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous 5FU infusion [10] or in combination with other anticancer drugs, FAM [11], FAMTX [7] have been used for chemotherapy of advanced gastric cancer. Recently, Ajani reported that DCF therapy (a combination chemotherapy using docetaxel, CDDP and 5FU) showed a significant better survival than CF (CDDP þ 5FU) therapy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment regimens have been developed (5,6,9) and have improved the survival of patients with advanced or recurrent gastric cancer (21). The rationale for the design of the combination therapy of docetaxel and S-1 was the significant Comparison of OS in patients between the curative resection and palliative groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among combined regimens for systemic chemotherapy for gastric cancer, the most widely used is the FAM combination [5-fluorouracil (5-FU), doxorubicin and mitomycin C] (Macdonald et al, 1980;Haim et al, 1982); a number of FAM modifications, involving the replacement of mitomycin with other drugs or of doxorubicin with epidoxorubicin, have also been investigated (Ogawa et al, 1990;Havlin et al, 1992). In addition, the combination of etoposide, doxorubicin and cisplatin (EAP) as well as the biochemical modulation of 5-FU activity by the addition of leucovorin (Bruckner et al, 1991;Kornek et al, 1992) have proved highly efficacious.…”
mentioning
confidence: 99%